Creative Union as the Mechanism of the Ideological Censorship in Lithuania in 1956–1980 - Ūsaitė, Kristina (Genocidas ir rezistencija, 2005)
The communist "cultural revolution" was realised as a whole-inclusive permanent process which aimed to destroy any individuality and to apply all forms of human self-expression to collectivism. One of the main to achieve this was an overall control of the artistic creation. Referring to the archival materials, the writing attempts to reveal the administrative and control mechanism of one of the lowest branches of the ideological censorship system, the creative unions, which operated in Lithuania in 1956–1980. Following concrete aspects of the organisational structure (membership in a creative union, work with the young artists, functionality of the creative sections and commissions founded under the union boards, ideological control and political education of the members) it analyses the scope of the ideological control functions assigned to creative unions and describes the influence of the leaders of the creative organisations on the cultural policy.In the thirties of the 20th century after the change in the legal status of the creative unions and associations, the parties took open and direct control over the creative unions. The creative unions in Lithuania were only territorial branches of analogous institutions of Moscow; their subordinations and organisational structure was based on a democratic centralised system common to the entire Soviet political system. The analysis of the organisational structure of the creative unions in a certain scope reflects the institutional activity peculiarities of the artists and their organisations. The fact that creative employees were concentrated according to territories and subjects (sphere) evidences that the priority was given for organisational issues. The artistic interests, approaches and creeds of members of the above mentioned organisations, uniting individualities and groups of the artists, encouraging their creative activeness and artistic searches did not have any influence on the organisational structures. Although officially the number of sections and commissions in the creative unions established under the boards of the LSSR creative unions, most of them were operating spontaneously, depending on the political conjuncture and limiting their work to the considerations over economic-financial issues. A little more independent were the sections and commissions in the unions of artists and composers. The primary party organisations responsible for the "creative-ideological" qualifications of the members of creative unions, due to unfavourable low general percentage of members of a certain creative union and members of its party organisation were unable to solve the question of political education. In the sixties, having assigned it to the creative sections, all until the end of the analysed period the problem continued to remain only formal. The most intense institutional development of creative unions took place at the end of the sixties-beginning of the seventies.Preconceived censorship was mostly developed in the organisation uniting the writers. The work with the beginning writers was extremely thoroughly organised. To help doing this there were the commissions for work with young artists that formed the base of the "internal censor" and the sections of young artists. A little less controlled were the representatives of the "pure" arts, the artists and composers. They had more independence. Establishment of the sections of young artists and commissions for work with young artists in the middle of the seventies was more determined by the changing political conjunctures. Moreover, it was often the very personalities of the leaders of the creative unions that influenced the cultural policy. The one taking most care of its members was the board of the LSSR artists' union led by a liberally oriented chairman J. Kuzminskas. A similar situation also developed in the LSSR composers' union which managed to remain free and independent when it concerned creative issues. Unlike the unions of artists and composers, the leaders of the writers' union were more subjected to the political conjuncture and almost did not consider the real needs of its members.
Keywords: Soviet culture; cenzorship; communist indoctrination; creative unions